Relationship between Anxiety and Interleukin 10 in Female Soccer Players with and Without Premenstrual Syndrome (PMS) - Foster, Roberta; Vaisberg, Mauro; Araújo, Maíta Poli de; Martins, Marcia Aparecida; Capel, Tiago; Bachi, Andre Luis Lacerda; Bella, Zsuzsanna Ilona Katalin de Jármy-Di (Revista Brasileira de Ginecologia e Obstetrícia / RBGO Gynecology and Obstetrics, 2017)
Objective To investigate the level of anxiety and its relationship with interleukin (IL)-10 (anti inflammatory cytokine that modulates mood swings) in a group of female soccer players.Methods Fifty-two eumenorrheic soccer players were evaluated (age 19.8 ± 4.7 years). The presence of premenstrual syndrome (PMS) and phases of the menstrual cycle were determined by a daily symptom report (DSR) kept for 3 consecutive months. The concentration of cytokine IL-10 was determined from urine samples collected at four moments: at the follicular and luteal phases of the menstrual cycle, and before (pre) and after (post) the simulated game, and it was quantified by flow cytometry (Luminex xMAP - EMD Millipore, Billerica, MA, USA). The level of anxiety was determined through the BAI anxiety questionnaire answered by all athletes at the same time of the urine collection. The Student t-test, analysis of variance (ANOVA) and Pearson correlation with significance level at 5% were used for data analysis.Results We showed that the prevalence of PMS among female soccer players is similar to that reported in the literature. In addition, we showed that the group with PMS has a higher level of anxiety compared with group without PMS (p = 0.002). Interleukin-10 analysis in players without PMS revealed that there was a significant decrease in the level of this cytokine before the game during the luteal phase when compared with the follicular phase (p < 0.05). The correlation analysis between IL-10 and anxiety showed a negative correlation post-game in the luteal phase in the group without PMS (p = 0.02; r = -0.50) and a positive correlation post-game in the luteal phase in PMS group (p = 0.04; r = 0.36).Conclusion Our results suggest that IL-10 may contribute to reduce anxiety in the group without PMS. This could be attributed to the fact that no IL-10 variation was observed in the group with PMS, which presented higher anxiety symptoms when compared with the group without PMS.
Keywords: soccer; menstrual cycle; premenstrual syndrome; inflammation; cytokine